Качество работы опросной сети: к постановке проблемы - Стукало, С. (Социология: теория, методы, маркетинг, 2004)
The article deals with the work quality system of the interviewers network. The quality system contains demands to the survey procedures and also the administrative conditions covering all components of interviewers network functioning.